Clinical researchWhy does intensive insulin therapy implemented at the onset of type 1 diabetes not decrease prevalence of diabetic microangiopathy? - Araszkiewicz, Aleksandra; Zozulińska-Ziółkiewicz, Dorota; Trepińska, Magdalena; Wierusz-Wysocka, Bogna (Archives of Medical Science, 2008)
Introduction: The aim of this study was to assess the incidence and predictors of nephropathy and retinopathy in prospective observation of type 1 diabetic patients treated with intensive functional insulin therapy (IFIT) from the onset of disease. Material and methods: 86 type 1 diabetic patients, mean age 23.4±5.1 years, were investigated once a year. The mean follow-up of this study was 7.1±1.5 years. We analyzed the association between various clinical features and subsequent diagnosis of diabetic microangiopathy. Results: We detected background retinopathy in 17 subjects (20%) and positive microalbuminuria in 13 patients (15%). Five patients had both retinopathy and positive microalbuminuria. The development of retinopathy and microalbuminuria was associated with lower knowledge about diabetes (respectively, RR=3.71, 95% CI: 1.15-12.01, P=0.02 and RR=4.33, 95% CI: 0.98-19.10, P=0.04), worse self-monitoring of blood glucose (respectively, RR=5.50, 95% CI: 2.00-15.11, P=0.0003 and RR=2.86, 95% CI: 1.13-7.24, P=0.04), lower HDL cholesterol level (respectively, RR=3.06, 95% CI: 1.36-6.87, P=0.01 and RR=4.85, 95% CI: 1.95-12.00, P=0.002) and higher diastolic blood pressure (respectively, RR=7.42, 95% CI: 2.11-26.15, P=0.002 and RR=10.62, 95% CI: 3.32-33.96, P=0.0001). Additionally the risk of the development of microalbuminuria was associated with BMI (RR=2.99, 95% CI: 1.10-8.10, P=0.04), postprandial glycaemia (RR=10.66, 95% CI: 1.49-7.61, P=0.001) and high triglyceride level (RR=4.52, 95% CI: 1.97-10.33, P=0.01). Conclusions: The presented data show that the development of microangiopathy in type 1 diabetic patients treated with intensive functional insulin therapy from the onset of the disease was associated with low diabetic knowledge and signs of insulin resistance.